Orthostatic myoclonus after brain tumor radiation: Insights from two lesional cases. (August 2017) - Cutsforth-Gregory, Jeremy K.; Hammack, Julie E.; Matsumoto, Joseph Y.
Abstract: Introduction: Orthostatic myoclonus (OM) is a recognized syndrome of gait unsteadiness accompanied by lower limb myoclonus provoked by the assumption of an upright posture. OM typically affects the elderly and is often associated with neurodegenerative disease. We sought to review the clinical and electrophysiologic characteristics of OM due to brain tumor treatment, the first reported lesional cases of this rare disorder. Methods: The database of the Mayo Clinic Rochester Movement Disorders Laboratory was searched for all patients diagnosed with OM from January 2007 to December 2016. All available clinical, radiographic, and surface electromyographic data were reviewed, and patients with a history of primary or metastatic brain tumor were analyzed. Results: Two patients with OM and brain tumor were identified; both had undergone tumor resection and targeted brain radiation. Both patients complained of unsteadiness while walking and recurrent falls. Tumor pathology (atypical meningioma, gliosarcoma) was centered in the frontal lobe and extended to the supplementary motor area (SMA), pre-SMA, or prefrontal cortex. Medications did not improve gait. Conclusion: Two cases of brain tumor-related OM suggest that degeneration of frontal motor programming circuits underlies the pathophysiology of OM. Highlights: In orthostatic myoclonus, lower limb myoclonus occurs only in upright posture. OM is most often associated with diffuse neurodegenerative disease. Two patients with frontal lobe tumors developed OM after resection and radiation. Lesional cases suggest OM may be due to disruption of frontal lobe motor circuits.